Functional and aesthetic evaluation of adjacent tissue flap repairing defects of oral commissure area - Xuewei Jia; Xiaomeng Xue; Fayu Liu; Pai Pang; Yang Yue; Menghan Li; Zhongzheng Qi; Changfu Sun (BMC Oral Health)
Abstract Background From a functional and aesthetic point of view, the oral commissure is the most difficult area to reconstruct in lip defects. It is a very complex and challenging task to rebuild the function and appearance of the oral commissure area with high quality.The aim of this paper is to discuss and compare the results of different methods for the reconstruction of defects in oral commissure area. Methods This study used five commonly used adjacent tissue flaps to reconstruct and evaluate postoperative oral function and appearance in patients who underwent repair of defects in the oral commissure region between September 2015 and June 2024. The primary outcomes were salivation, oral function, speech intelligibility, reconstructed lip tactility, Patient and Observer Scar Assessment Scale (POSAS) and patient postoperative quality of life evaluation. Results A total of 55 patients underwent surgical reconstruction of defects in oral commissure. At 6 months postoperatively, the McGregor and Colmenero groups demonstrated more statistically excellent oral motility compared to the other groups (p = 0.028).There was no significant difference in the effect of the different reconstruction on the patients’ speech expression and flap tactile sensitivity. The aesthetic outcomes were favorable in both groups. Quality of life was at a higher level in patients who underwent reconstruction with the Estlander, McGregor and Colmenero flaps (p = 0.036). Conclusion Taking into account the differences between each reconstruction method, the Estlander flap is the preferred method for small and medium-sized defects, the McGregor and Colmenero flap can better restore motor function.The methods of repairing defects of the oral commissure area described in our study do not differ significantly in speech expression, flap tactile sensitivity, or aesthetic outcomes. Postoperative quality of life is higher in patients reconstructed with Estlander, McGregor and Colmenero flap repairing.